Investigation of antibody-mediated neutralization and protection against wild-type yellow fever virus by human monoclonal antibodies - Saunders, Danielle R. D. (Kansas State University, 2022)
Yellow fever virus (YFV) is the prototype flavivirus that causes severe viscerotropic disease. The disease yellow fever (YF) leads to a high mortality rate in immunologically naïve humans and New World primates in tropical South America. While the safe and effective live-attenuated 17D vaccine is available for disease control, recent outbreaks and vaccine shortages has led to a growing interest in the development of therapeutics and second-generation YF vaccines. To rationally design candidate vaccines that are not inferior to the 17D vaccine, a thorough understanding of the mechanisms of protection against wild-type (wt) strains of YFV is needed, especially neutralizing antibodies that are the correlate of protection elicited by the YF 17D vaccine. Although previous studies have indicated neutralizing antibody responses elicited by the 17D vaccine are type-specific (i.e., only neutralize YFV and does not cross-react with other flaviviruses) and mainly target the envelope (E) protein, few studies have investigated human monoclonal antibodies (mAbs). Therefore, a significant gap in knowledge exists on how a single dose of the 17D vaccine can confer long-lasting immune protection against the seven known genotypes of wt YFV in humans. The research described in this dissertation was undertaken to investigate the antibody-mediated neutralization and protection against wt YFV through the characterization of two YFV type-specific neutralizing human mAbs isolated from 17D vaccinees. Three approaches were taken to test the central hypothesis that YFV type-specific neutralizing human mAbs isolated from 17D vaccinees recognize epitope(s) on the E protein and can neutralize and protect against wt YFV infection. First, the neutralizing potency of two human anti-YFV mAbs isolated from 17D vaccinees (mAb-29 and mAb-32) were quantified against the 17D-204 vaccine substrain and the representative strains of four genotypes of wt YFV including West Africa I genotype (BA-55 strain), West Africa II genotype (Asibi strain), South America I genotype (JSS strain), and South America II genotype (1899/81 strain) to demonstrate both mAbs exhibit YFV type-specific neutralizing activities. The four-fold difference in neutralizing titers between the 17D-204 and wt Asibi strains was observed and provided the basis for the epitope characterization using the recombinant 17D-204 strain, Asibi strain, and four chimeras constructed to replace three individual domains of the E protein (ED) of the Asibi strain with the corresponding region in the 17D strain. The antigenic sites recognized by mAb-29 and mAb-32 were delineated by examining the neutralizing potency against recombinant Asibi strain, 17D strain, and Asibi-17D chimeras. The simultaneous replacement of EDI and EDII from the 17D strain altered the sensitivity of the Asibi strain to the neutralization of mAb-29 and mAb-32. Therefore, both mAbs target conformational epitope(s) consisting of amino acids across the EDI and EDII. Lastly, the prophylactic passive protection of mAb-29 and mAb-32 against neurotropic and viscerotropic YF disease in mice was determined. Both mAbs conferred full protection against neurotropic disease caused by intracerebral challenge of the 17D vaccine strain in outbred CD-1 mice. MAb-29 and mAb-32 were further shown to partially protect against neurotropic disease caused by intracerebral challenge of the wt Asibi strain in CD-1 mice by increasing the median survival time and decreasing the brain viral load compared to the control group. Importantly, mAb-29 and mAb-32 demonstrated partial protection against viscerotropic disease caused by intraperitoneal challenge of the wt Asibi strain in C57BL/6 mice lacking type-I and type-II interferon receptors (C57BL/6-IFNAR[superscript -/-]-IFNGR[superscript -/-]), referred to as AG6 mice, by increasing the median survival time and significantly reducing the tissue viral load in the brain, liver, kidneys, spleen, and mesenteric draining lymph nodes compared to the control group. Collectively, the completion of these projects advances our understanding of antibody-mediated neutralization and protection against wt YFV in humans. Both human anti-YFV mAbs belong to the YFV type-specific neutralizing antibody group relevant to the protective immunity elicited by YF 17D vaccines. The mAbs target multiple domains in the E protein, suggesting that at least one conformational epitope is responsible for eliciting neutralizing antibody responses in 17D vaccinees. Significantly, passive transfer of mAb-29 and mAb-32 confers protection against the wt YFV Asibi strain, directly demonstrating the involvement of human YFV type-specific neutralizing antibodies in the protective immunity against wt YFV challenge in vivo. Results from this dissertation research demonstrated the utility of human anti-YFV mAbs isolated from 17D vaccinees for the investigation of protective immunity against wt YFV and identified two anti-YFV mAbs that can potentially be evaluated as candidate therapeutic antibodies.
Keywords: Yellow fever virus; Monoclonal antibodies; Mouse model; Epitope characterization; Yellow fever 17D vaccine; Antibody-mediated neutralization